Harper's illustrated biochemistry /;Principles of biochemistry - Voet, Donald; Rodwell, Victor W.,;Bender, David A.,;Botham, Kathleen M.,;Kennelly, P. J.,;Weil, P. Anthony,;Voet, Judith G.;Pratt, Charlotte W. (Hoboken, N.J. : John Wiley & Sons, 2013)
Presents integrated coverage of biochemical disease and clinical information to provide a clear, succinct review of the fundamentals of biochemistry that every student must understand in order to succeed in medical school.
Structures & functions of proteins & enzymes -- Enzymes: kinetics, mechanism, regulation & bioinformatics -- Bioenergetics -- Metabolism of carbohydrates -- Metabolism of lipids -- Metabolism of proteins & amino acids -- Structure, function, & replication of informational macromolecules -- Biochemistry of extracellular & intracellular communication -- Special topics (A) -- Special topics (B) -- Special topics (C).
A Lange medical book;Previous ed.: 2008.
Includes bibliographical references and index.;Includes bibliographical references and index.
Keywords: Biochemistry. -- Clinical biochemistry; Biochemistry. -- Metabolism